International market for forest carbon offsets: how these offsets are created and traded. ASB lecture note 14 - Jindal, Rohit; Namirembe, Sara (My University, 2012)
This lecture note explains how carbon credits or offsets are generated from the forestry sector - both in terms of growing new trees as well as protecting existing ones, and how they are traded in international markets. It is important to note that these projects and the resultant offsets are only a part of a long set of solutions that the international community is considering to address climate change. We also explain why in spite of the surge in international carbon markets, actual trading in forestry carbon offsets remains low. The lecture note is primarily meant to share information among ICRAF’s (World Agroforestry Centre) local partners in South East Asia and Africa on how to engage in international markets for forestry carbon offsets. However, the note will also be useful for government officials, NGO functionaries, private sector operators, and community representatives in other developing countries who wish to access international carbon market to sell locally produced carbon offsets from forestry and other conservation oriented activities, or even to just understand how the market operates.
International market for forest carbon offsets: how these offsets are created and traded. ASB lecture note 14
Keywords: carbon credits; climate change; farmers; Congo basin; forestry